2014
DOI: 10.1080/19942060.2014.11015514
|View full text |Cite
|
Sign up to set email alerts
|

ISPH Modelling and Analysis of Fluid Mixing in a Microchannel with an Oscillating or a Rotating Stirrer

Abstract: ABSTRACT:In the present study, we apply a robust Incompressible Smoothed Particle Hydrodynamics method improved by advanced second-order discretization in order to examine active micromixers equipped with a rotating or an oscillating stir-bar. Since it has a Lagrangian nature and it is based on particles, Smoothed Particle Hydrodynamics is an appropriate and convenient method for the moving boundary and for one-way coupled fluidsolid interactions. However, this method has not been applied to simulate active mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Shamsoddini, et al simulated a micromixer equipped with a blade using the hydrodynamic method of incompressible particles and evaluated the performance of the micromixer in terms of mixing efficiency and type of blade state. They showed that the performance of the cross blade was better than that of the straight blade [64]. Nguyen and Wu conducted a review study on micromixers, their types, and applications [59].…”
Section: Micromixingmentioning
confidence: 99%
“…Shamsoddini, et al simulated a micromixer equipped with a blade using the hydrodynamic method of incompressible particles and evaluated the performance of the micromixer in terms of mixing efficiency and type of blade state. They showed that the performance of the cross blade was better than that of the straight blade [64]. Nguyen and Wu conducted a review study on micromixers, their types, and applications [59].…”
Section: Micromixingmentioning
confidence: 99%
“…Shifting particle is a remedy for these unfavorable phenomena in the SPH method originally proposed by Xu et al (2009) and Shadloo et al (2011) from the different point of view and is extended to multi-phase flow (Shadloo et al 2013a(Shadloo et al , 2013b. To prevent these problems, a shifting algorithm which was previously examined by Shamsoddini et al (2014) has been applied. Two rows of dummy particles are arranged near each wall boundary, the velocity of each dummy particle calculated by its corresponding wall particles.…”
Section: Time Integrationmentioning
confidence: 99%
“…Due to its intrinsic complexities and importance of the fluid flow and heat transfer and more specifically, the suppression of the vortices shedding around a bluff body has been the subject of several studies in many practical engineering applications, such as flows past an air-plane, a submarine, and an automobile, heat exchanger systems, electronic cooling, gas turbine blades (Florides et al, 2007;Harte et al, 2007;Monat et al, 2018;Shamsoddini et al, 2014). Thus, a host of experimental and numerical investigations has been carried out, during the last years, to understand the flow and heat transfer past of square cylinders, circular or any other geometric shapes of a cylinder in cross flows with or without a control plate (Abbasi et al, 2014;Dey, 2021;Dhiman et al, 2005;Doolan, 2009;Guo et al, 2020;Islam et al, 2015;Koutmos et al, 2004;Kumar et al, 2015;Rashidi et al, 2015;Rashidi et al, 2016;Sohankar et al, 2018;Turki, 2008;Vamsee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%